Leptochlorella corticola gen. et sp. nov. and Kalinella apyrenoidosa sp. nov.: two novel Chlorella-like green microalgae (Trebouxiophyceae, Chlorophyta) from subaerial habitats - Neustupa, Jiří; Němcová, Yvonne; Veselá, Jana; Steinová, Jana; Škaloud, Pavel (International journal of systematic and evolutionary microbiology, 2013)
The diversity of green microalgae in subaerial habitats remains largely unexplored and a number of new genus- and species-level lineages have been discovered recently. The traditional green algal genus, Chlorella, which accommodated coccoid unicellular green algal species with globular to oval cells, reproducing entirely by autospores, has been found to be polyphyletic. In this study, we provide a detailed characterization of two strains of microalgae isolated from tree bark in the Mediterranean. These algae share the general Chlorella-like morphology and their 18S rRNA and rbcL gene sequences place them in the Trebouxiophyceae. Strain CAUP H8401 forms an independent trebouxiophycean lineage, together with three previously published 18S rRNA gene environmental sequences of undescribed microalgae, which were retrieved from profoundly different habitats. In contrast, strain CAUP H7902 is related to Kalinella bambusicola in the Watanabea clade of the Trebouxiophyceae on the basis of its 18S rRNA gene sequence. This relationship is also supported by the rbcL gene sequence, acquired from the type strain of K. bambusicola. The investigated strains are described as representatives of a novel species in a new genus, Leptochlorella corticola gen. et sp. nov., and a novel species, Kalinella apyrenoidosa sp. nov., according to the International Code of Nomenclature for Algae, Fungi and Plants.
Keywords: Středomoří; DNA, Algal; RNA, Ribosomal, 18S; Plant Bark; vavřín; kůra rostlin; Cupressus; cypřiš (rod); RNA, Ribosomal, 16S; Slovenia; Molecular Sequence Data; Chlorophyta; DNA řas; Phylogeny; Laurus; Slovinsko; Mediterranean Region; molekulární sekvence - údaje; RNA ribozomální 18S; Sequence Analysis, DNA; sekvenční analýza DNA; fylogeneze; RNA ribozomální 16S